Analysis of the impact of various finish line designs and occlusal morphologies on the accuracy of digital impressions - Aylin Gunel; Mustafa Baris Guncu; Sema Merve Uzel; Guliz Aktas; Hale Arikan; Natalia Reiss; Ilser Turkyilmaz (Elsevier, 2023)
Background/purpose: Recent advancements in dental technology has led clinicians to convert from traditional methods to digital workflows. The purpose of this study was to analyze the effect of various finish line designs and occlusal morphologies on the accuracy of digital impressions. Materials and methods: Six maxillary molar crown preparations were designed by using a digital sculpting software program. The samples differed in finish line design and occlusal surface morphology. Three different finish line designs (shoulder, chamfer, and shoulder with internal round angle) and two different occlusal morphologies (sharp and rounded) were used, giving six groups. Using three different intraoral scanners, each group was scanned and compared with a reference scan obtained from an industrial scanner. The accuracy of each scan was studied, and the data were statistically analyzed. Results: A total of 180 scans were acquired by utilizing three different intraoral scanners. The reference scan was compared with the scans from each group and overall differences (marginal, axial, and occlusal) were assessed. A crown preparation with a chamfer finish line showed the lowest marginal discrepancy of 13.2 ± 4.18 μm while preparation with a shoulder finish line reported the highest discrepancy of 34.8 ± 7.9 μm (P < 0.05). Also, the occlusal discrepancies of the samples with rounded and sharp occlusal morphologies were 12.55 ± 3.09 μm and 19.13 ± 2.3 μm, respectively (P < 0.05). Conclusion: It has been suggested that chamfer finish line design and rounded occlusal anatomy may produce more accurate digital impression for single crown restorations.